Development of image transmission using vector quantization source coding and QPSK OFDM scheme - 444689 Shia, Sook Sian (Skudai : Universiti Teknologi Malaysia, 2003)
Project Paper (Bachelor of Electrical Engineering (Telecommunication)) - Universiti Teknologi Malaysia, 2003